Transference of three Mexican species of Talinum Adans. to Phemeranthus Raf. (Portulacaceae) - Ocampo Acosta, Gilberto (Instituto de Ecología, A.C., 2002)
During preparation of the treatment of Portulacaceae for Flora del Bajío y de Regiones Adyacentes, it was determined that some species situated in genus Talinum require transfer to Phemeranthus, so in this paper the following new combinations are proposed: P. mexicanus (Hemsley) G. Ocampo, P. multiflorus (Rose & Standley) G. Ocampo and P. napiformis (DC.) G. Ocampo. In addition, the description for P. mexicanus is enlarged.